(untitled) (Aptisi Transactions on Technopreneurship (ATT), 2023)
This research aims to assess the impact of the clarity of budget objectives and reporting systems on government performance accountability, with accounting control serving as a moderating factor. The study was conducted within the Wonosobo Regency Regional Organization. Purposive sampling was employed to select 75 respondents, comprising officials responsible for financial reporting and accountability within their roles, including the Head of Finance, finance staff, and treasurer. Multiple linear regression was utilized for data analysis. Empirical evidence supports the notion that the clarity of budget goals and reporting systems has a positive influence on government agency performance accountability. Through moderation analysis, it was empirically demonstrated that accounting control can act as a moderating variable, negatively affecting the influence of budget goal clarity on agency performance responsibilities. However, accounting control can also serve as a moderating variable, positively affecting the influence of reporting systems on government performance.